The Influence of Financial Knowledge, Financial Attitude, Financial Self-Efficacy, Financial Well-Being, and Impulsive Buying on Saving Behavior Among Working People in Kubu Raya Regency - Lisa Amalia; Dedi Hariyanto; Heni Safitri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine the influence of financial knowledge, financial attitudes, financial self-efficacy, financial well-being, and impulsive buying on the saving behavior of people working in Kubu Raya Regency. This study uses a causal associative method. This study used a sample of 150 respondents with a purposive sampling technique. The correlation coefficient was 0.786, indicating a strong correlation between financial knowledge, financial attitude, financial self-efficacy, and impulsive buying on saving behavior. The coefficient of determination shows a value of 0.618, meaning that 61.8% indicates that saving behavior is influenced by financial knowledge, financial attitude, financial self-efficacy, and impulsive buying, while 38.2% is attributed to other variables not examined in this study. The results of the simultaneous test show that financial knowledge, financial attitude, financial self-efficacy, financial well-being, and impulsive buying have a simultaneous effect on the savings behavior of people working in Kubu Raya Regency. The partial test results show that the variables financial knowledge, financial attitude, financial self-efficacy, and financial well-being have a positive and significant effect on savings behavior, while impulsive buying does not have a significant effect on savings behavior.